Impact damage investigation on composite laminates: comparison among different NDT methods and numerical simulation. (14th July 2015) - Pagliarulo, V; Rocco, A; Langella, A; Riccio, A; Ferraro, P; Antonucci, V; Ricciardi, M R; Toscano, C; Lopresto, V
Abstract: The aim of this paper is to investigate the ability of different NDT techniques to detect and evaluate barely visible and non-visible impact damage on composite laminates. Firstly, a conventional ultrasound technique was adopted to investigate the delamination in carbon fibre laminates after low velocity impact s. Then the results were compared with a thermographic and holographic analysis, as well as a theoretical simulation of the expected delamination. The results were compared and discussed. Overall a good agreement was found between the data obtained by the different techniques. Furthermore, the true values of the damage parameters were confirmed by DT performed on the samples.